Concomitant use of blinatumomab and donor lymphocyte infusion for mixed-phenotype acute leukemia: a case report with literature review. (21st February 2019) - Durer, Seren; Durer, Ceren; Shafqat, Madeeha; Comba, Isin Yagmur; Malik, Saad; Faridi, Warda; Aslam, Shehroz; Ijaz, Awais; Tariq, Muhammad Junaid; Fraz, Muhammad Asad; Usman, Muhammad; Khan, Ali Y; et al.
Blinatumomab and donor lymphocyte infusion (DLI) combination is a promising cancer therapy, whereby blinatumomab might achieve an initial reduction in leukemic-cell burden using T cells, and after tumor clearance, DLI can potentially stimulate the donor immune system to achieve longer lasting remission. Here, we present a 51-year-old female with mixed phenotype acute leukemia who had a hematologic relapse 3 months after she received total body irradiation-based myeloablative allogeneic hematopoietic stem cell transplantation from an unrelated human leukocyte antigen matched (10/10) donor and achieved complete remission with minimal residual disease negativity by multi-parameter flow cytometry using the combination of blinatumomab and DLI. To the best of our knowledge, this is the first report to describe the use of blinatumomab and DLI combination therapy in the treatment of B/myeloid mixed phenotype acute leukemia.